Efficient Gaussian sampling for RLWE-based cryptography through a fast Fourier transform - Barbado Júnior, Márcio (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2022: Anais do XXII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2022.224430, 2022)
Quantum computing threatens classical cryptography, leading to the search for stronger alternatives. The cryptographic approach based on lattices is considered as a viable option. Schemes with that approach use Gaussian sampling, a design which brings along two concerns: efficiency and information leakage. This work adresses those concerns in the RLWE formulation, for digital signatures. Efficiency mitigation uses the central limit theorem, and the Walsh–Hadamard transform, whereas the information leakage risk is reduced via isochronous implementation. Up to 2 23 samples are queried, and the results are compared against those of a cumulative distribution table sampler. Statistical metrics show the suitability of the presented sampler in a number of contexts.